Odpowiedzi

2009-12-19T18:47:17+01:00
A) log x = 0
logx=log1
x=1

b)log₂x=5
log₂x=5log₂2
log₂x=log₂2⁵
x=32

c)log₂ [log₂ (log₂x)] = 1
log₂ [log₂ (log₂x)] =log₂2
log₂ (log₂x) =2
log₂ (log₂x)=2log₂2
log₂ (log₂x)=log₂2²
log₂ (log₂x)=log₂4
log₂x=4
log₂x=4log₂2
log₂x=log₂2⁴
x=16

d) log₂x = log2 10 + log₂5 - log₂ 25
log₂x = log₂(10*5:25)
log₂x = log₂2
x=2
Najlepsza Odpowiedź!
2009-12-19T18:47:28+01:00
A) log x = 0
x=10⁰
x=1

b)log₂x=5
x=2⁵
x=32

c)log₂ [log₂ (log₂x)] = 1
log₂ [log₂ (log₂x)]=log₂ 2
log₂ (log₂x)=2
log₂ (log₂x)=log₂4
log₂x=4
x=2⁴
x=16

d) log₂x = log₂ 10 + log₂5 - log₂ 25
log₂x=log₂(10*5:25)
log₂x=log₂2
x=2